APIs in bibliometric contexts: a basic introduction and comprehensive corpus - Torres-Salinas, Daniel; Arroyo-Machado, Wenceslao (Anuario ThinkEPI, 2022)
Bibliometrics is facing an intricate universe of data that is constantly changing and expanding, with a wide ecosystem of data sources in which it is easy to get lost. In this complex setting, APIs are positioned as the perfect solution to deal with this heterogeneity and to obtain adapted data. Although APIs have not come as a surprise, it is now time to highlight their value and promote their use, which will make them easier to utilize. In this paper we therefore take a practical approach to APIs in the bibliometrics field. To this end, we provide an introduction to APIs and the new work processes that their use entails. We also offer a corpus in which we compile 49 APIs of interest to bibliometricians, organized by type and access, as well as programming packages in R and Python that facilitate their use.